Contactless Smart Body Temperature Scanner System - Ku, Alvin Zi Qian (2021)
Fever is the early sign of infection. Therefore, body temperature screening has always been deployed to detect suspected individuals with infectious diseases. The current temperature scanner is distance-dependent, which introduces errors when the temperature is measured at various distances. Also, some contactless temperature scanners can only measure body temperature at a fixed distance. Besides, many studies are mainly focused on building additional features for the temperature scanner system rather than improving the performance of the temperature sensor. In addition, the typical contactless temperature scanner is also not equipped with an automatic data logging feature for contact tracing purposes. This project aims to set up a low-cost, functional distanceindependent contactless temperature scanner system with an automated data logging feature. Next, a calibration approach is introduced to ensure accurate contactless temperature measurement at various distances. The proposed system consists of integrating subsystems, which are the temperature scanner system and data logging system. The prototype is first calibrated at a fixed distance of 3 cm to improve its accuracy. It is then further calibrated at multiple distances of 3.5 cm, 4 cm, 4.5 cm, and 5 cm to obtain a minimal trade-off between measuring distance and accuracy. The data logging feature can store user’s information such as barcode, temperature, check-in time, and date on an SD card. The alarming system is activated if the user’s temperature is not within the normal range. Overall, the prototype developed can provide temperature measurement with an accuracy of ±0.2 °C and automatically record the user’s information. The prototype is envisioned to be deployed at public or private places, which a barcode is used for identification purpose.